165 CLINICAL IMPACT OF PREOPERATIVE SERUM P53 ANTIBODY TITERS IN 1, 487 PATIENTS WITH ESOPHAGEAL CARCINOMA: A MULTI-INSTITUTIONAL STUDY. (17th September 2021) - Suzuki, Takashi; Yajima, Satoshi; Okamura, Akihiko; Yoshida, Naoya; Taniyama, Yusuke; Murakami, Kentarou; Okura, Yu; Nakajima, Yasuaki; Yagi, Kouichi; Fukuda, Takashi; Ogawa, Ryo; Hoshino, Isamu; et al.
Abstract: : Although previous reports showed clinicopathological and diagnostic significance of serum p53 antibody in esophageal squamous cell carcinoma, all those reports analyzed only 100 to 200 patients at single institute. This study was designed as a multi-institutional study promoted by the Japan Esophageal Society to elucidate the clinical significance of serum p53 antibody in esophageal cancer treatment. Methods: A total of 1, 487 patients, from 15 hospitals of Japan, with esophageal carcinoma surgically treated between 2008 and 2016 were enrolled in this retrospective study. We used 1.30 U/ml as a cutoff for classifying patients into positive and negative groups. And we attempted to analyze only positive cases. A receiver operating characteristic curve was constructed to assess serum p53 antibody cutoff levels to differentiate poor prognosis. We used 9.82 U/ml as a cutoff for classifying patients into low and high groups. Univariate and multivariate analyses were used to evaluate the clinicopathological and prognostic significance of pretreatment level of serum p53 antibody. Results: There were significant relationships between serum p53 antibody level and tumor depth (p = 0.002), nodal status (p = 0.027) and pathological stage (p = 0.002). The positive serum p53 antibody group had a no significantly worse overall survival than that of the negative group (p = 0.699). The high serum p53 antibody group had a significantly worse overall survival than that of the low group (p = 0.024). However, the difference was not significant in the multivariate analysis (p = 0.137). Conclusion: Although high level (>9.82 U/ml) of pretreatment serum p53 antibody might be associated with poor prognosis for patients with esophageal cancer, high serum p53 antibody was not an independent risk factor.